Application of Bag-Controlled Release Fertilizer Facilitated New Root Formation, Delayed Leaf, and Root Senescence in Peach Trees and Improved Nitrogen Utilization Efficiency - Zhang, Yafei; Luo, Jingjing; Peng, Futian; Xiao, Yuansong; Du, Anqi (Frontiers in Plant Science, 2021)
It is very important to promote root growth and delay root and leaf senescence, improve nitrogen absorption and utilization efficiency, and improve the storage nutrition level of the tree, so as to improve the fruit quality and yield of peach. In this experiment, We compared and analyzed the effects of traditional fertilization and bag-controlled release fertilizer (BCRF) on the growth of shoots and roots, senescence of leaves and roots, and fruit yield and quality. Moreover, the impacts of BCRF on ammonia volatilization, nitrogen utilization rate, fine root turnover and plant storage nutrients were also investigated. Compared with conventional fertilizer use, the application of BCRF significantly promoted the shoot growth of young peach trees. Additionally, BCRF delayed leaf senescence and increased root activity in autumn. This increased the storage nutrients of the peach tree. Compared with traditional fertilizer, Ammonia volatilization reduced 54.36% under BCRF application situation. BCRF also promoted the occurrence of fine roots and decreased the annual turnover rate. A 15N tracer test showed that compared with traditional fertilizer, BCRF the nitrogen utilization efficiency increased 37.73% in peach trees under BCRF treatment, signiﬁcantly. The results from three consecutive years showed that application of BCRF increased the yield of individual plants by 21.35% on average compared to the yield from plants receiving equal amounts of fertilizer applied by spreading (FSA). Thus, BCRF can promote the occurrence of fine roots and decrease the root annual turnover rate in peach trees, and it also improves the utilization efficiency of fertilizer, reduces ammonia volatilization, delayes leaf senescence and enhances storage nutrition and fruit yield and fruit quality in peach trees.